Sosialisasi Penyediaan Air Bersih dengan Kejadian Diare di Wilayah Kerja Puskesmas Ujung Pandang Baru - K, Hairuddin; Yulis, Dian Meiliani; Serli, Serli; Yermi, Yermi; B, Muslimin; Ahmad, Muhammad Iqbal (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The limited supply of clean water to meet the needs of the community in the Jumpandang Baru Community Health Center area is a health problem and obstacle experienced by the community. With shortages and limitations of knowledge, facilities, infrastructure and economy, residents continue to use unhealthy water for household needs. Therefore, the community really needs to be given the knowledge and skills to process clean water to prevent diarrhea in the community. Community service activities in Clean Water Processing aim to: 1) increase knowledge about clean water and the culture of clean living in anticipation of diarrhea in the community, 2) provide technology skills for clean water processing processes in the community. This goal is achieved through activities in the form of outreach, counseling, training and the application of appropriate technology to process clean water. The results achieved are: 1) increased partner knowledge about the importance of clean water for health, 2) partners have the knowledge and skills to process clean water for households. 3). Diarrhea can be avoided so that people can live clean and healthy.